WAYS TO INCREASE THE EFFECTIVENESS OF THE MORAL AND PSYCHOLOGICAL TRAINING SYSTEM AND THE THEORETICAL MODEL OF ITS ORGANIZATION (Scientific journal of the Fergana State University, 2025)
The article discusses ways to improve the effectiveness of the system of moral and psychological training (hereinafter referred to as MPT) for military training cadets. Modern approaches to MPT are analyzed, problems are identified, and a theoretical model of its organization is proposed. The study uses methods of mathematical and statistical analysis to assess the impact of the proposed system-functional model on the level of moral and psychological stability of cadets. The results show that a systematic approach, including elements of personality-oriented and competence-based approaches, significantly increases the effectiveness of the MPT.